PENDIDIKAN SOCIAL JUSTICE DI MASA PANDEMI COVID-19 : PERTIMBANGAN DAN KEKHAWATIRAN - Septianita, Hesti; Tedjabuwana, Rosa; Utama, Alif Putra (LITIGASI, 2021)
The outbreak of the Covid-19 virus has caused disruptions across the globe. The table has turned drastically and unexpected. All aspects of life are impacted by this corona virus. The world, ready or not are forced to adapt with the situation. Legal schools have to conduct online learning. The concern should be paid to how social justice education can be done online when trying to sensitize the students towards social justice. The approach used in this research was juridical normative examining norms related to social justice learning. Conceptual approach was used to show views and analysis of problem solving on social justice learning through online method at undergraduate level to produce lawyers with legal professional skills. Therefore, traditional law school curricula provide chances for students to develop their skills. The impact is that online learning that can produce future litigators with the same or even better quality with the conservative method is still in doubt. The research concluded that some elements are missing from the online learning when teaching social justice to students such as professional skills and social emphathy. Keywords: Outbreak of Covid-19 Virus, Online Learning, Social Justice.